Economy Rempowerment for The Creative Community's Economy: A Case Study of Mask Connectors Business After Pandemic - Budimansyah, Budimansyah; Pratomo, Dimas; Rahma, Indry Damayanti (Jurnal Abdimas, 2023)
World Health Organization (WHO) explains that Coronaviruses infect the respiratory system. All activities are limited. Anxiety and panic certainly landed in the hearts of business people when the economic crisis spread to almost all countries in the world due to COVID-19. Consumers will only purchase primary goods and tend to avoid purchasing secondary, let alone tertiary goods, thus having an impact on the demand (supply) side. The slowing pace of the Indonesian economy will affect various economic sectors. So the author wants to tell the people in Pahoman Village, Enggal District, Bandar Lampung City, about the creative economy, so that it can be profitable and provide benefits to other people. The methods used are based on community service, such as socialization/counseling, training, mentoring, and interviews. This writing concludes that making mask connectors will still open up business opportunities after the pandemic. By conducting this training, people can be creative and develop a creative economy so that it can help generate ideas for entrepreneurship.